Analisis Kesulitan Guru Matematika dalam Proses Mengajar Kelas IV di Sekolah MI Sunan Giri Merjosari Lowokwaru Malang - Budi, Irwan Setia; Aini, Qurratul; Irawan, Wahyu Hengky; Abdussakir, Abdussakir (AS-SABIQUN, 2024)
Learning mathematics has become a polemic for some teachers considering the need for innovations to answer the challenges of the times. The development of the curriculum is a challenge for teachers in adjusting to the latest learning currents which are indirectly required to develop in planning and learning processes which often become a difficulty for teachers in self-development. The study aims to describe how the learning process leads to the difficulties of mathematics teachers in grade IV MI Sunan Giri Merjosari Lowokwaru Malang in detail. This research method uses qualitative with phenomenological types. Data and data sources were obtained from informants at the MI Sunan Giri Merjosari Lowokwaru Malang institution. The results of this study indicate that one of the difficulties experienced by teachers is in lesson planning, where the teacher has difficulty in allocating time, using learning resources and determining methods in adjusting learning material while in the learning process activities the teacher experiences a little difficulty in concentrating students while at the learning evaluation stage , the questions in the LKPD have not yet entered the realm of the Hots level. Difficulties come from several factors, one of which is the impact of curriculum changes, lack of training and lack of attention from the impact of curriculum changes, lack of training and lack of attention from the government. The difficulties experienced by teachers can be overcome in several ways, one of which is training, seminars, study tours where these methods are shortcuts to hone teacher competence.